Exploring biochar and fishpond sediments potential to change soil phosphorus fractions and availability - Mahmood, Mohsin; Wang, Yunting; Ahmed, Waqas; Mehmood, Sajid; Ayyoub, Anam; Elnahal, Ahmed S. M.; Li, Weidong; Zhan, Xin (Frontiers in Plant Science, 2023)
Phosphorus (P) availability in soil is paradoxical, with a significant portion of applied P accumulating in the soil, potentially affecting plant production. The impact of biochar (BR) and fishpond sediments (FPS) as fertilizers on P fixation remains unclear. This study aimed to determine the optimal ratio of BR, modified biochar (MBR), and FPS as fertilizer replacements. A pot experiment with maize evaluated the transformation of P into inorganic (Pi) and organic (Po) fractions and their contribution to P uptake. Different percentages of FPS, BR, and MBR were applied as treatments (T1–T7), T1 [(0.0)], T2 [FPS (25.0%)], T3 [FPS (25.0%) + BR (1%)], T [FPS (25%) +MBR (3%)], T5 [FPS (35%)], T6 [FPS (35%) +BR (1%)], and T7 [FPS (35%) + MBR (1%)]. Using the modified Hedley method and the Tiessen and Moir fractionation scheme, P fractions were determined. Results showed that various rates of MBR, BR, and FPS significantly increased labile and moderately labile P fractions (NaHCO3-Pi, NaHCO3-Po, HClD-Pi, and HClC-Pi) and residual P fractions compared with the control (T1). Positive correlations were observed between P uptake, phosphatase enzyme activity, and NaHCO3-Pi. Maximum P uptake and phosphatase activity were observed in T6 and T7 treatments. The addition of BR, MBR, and FPS increased Po fractions. Unlike the decline in NaOH-Po fraction, NaHCO3-Po and HClc-Po fractions increased. All Pi fractions, particularly apatite (HClD-Pi), increased across the T1–T7 treatments. HClD-Pi was the largest contributor to total P (40.7%) and can convert into accessible P over time. The T5 treatment showed a 0.88% rise in residual P. HClD-Pi and residual P fractions positively correlated with P uptake, phosphatase activity, NaOH-Pi, and NaOH-Po moderately available fractions. Regression analysis revealed that higher concentrations of metals such as Ca, Zn, and Cr significantly decreased labile organic and inorganic P fractions (NaHCO3-Pi, R2 = 0.13, 0.36, 0.09) and their availability (NaHCO3-Po, R2 = 0.01, 0.03, 0.25). Excessive solo BR amendments did not consistently increase P availability, but optimal simple and MBR increased residual P contents in moderately labile and labile forms (including NaOH-Pi, NaHCO3-Pi, and HClD-Pi). Overall, our findings suggest that the co-addition of BR and FPS can enhance soil P availability via increasing the activity of phosphatase enzyme, thereby enhancing plant P uptake and use efficiency, which eventually maintains the provision of ecosystem functions and services.